Loss of dysbindin-1, a risk gene for schizophrenia, leads to impaired group 1 metabotropic glutamate receptor function in mice - Bhardwaj, Sanjeev K.; Ryan, Richard T.; Wong, Tak Pan; Srivastava, Lalit K. (Frontiers in Behavioral Neuroscience, 2015)
The expression of dysbindin-1, a protein coded by the risk gene dtnbp1, is reduced in the brains of schizophrenia patients. Evidence indicates a role of dysbindin-1 in dopaminergic and glutamatergic transmission. Glutamatergic transmission and plasticity at excitatory synapses is critically regulated by G-protein coupled metabotropic glutamate receptor (mGluR) family members, that have been implicated in schizophrenia. Here, we report a role of dysbindin-1 in hippocampal group 1 mGluR (mGluRI) function in mice. In hippocampal synaptoneurosomal preparations from sandy (sdy) mice, that have a loss of function mutation in dysbindin-1 gene, we observed a striking reduction in mGluRI agonist [(S)-3,5-dihydroxyphenylglycine] (DHPG)-induced phosphorylation of extracellular signal regulated kinase 1/2 (ERK1/2). This mGluR-ERK1/2 deficit occurred in the absence of significant changes in protein levels of the two members of the mGluRI family (i.e., mGluR1 and mGluR5) or in another mGluRI signaling pathway, i.e., protein kinase C (PKC). Aberrant mGluRI-ERK1/2 signaling affected hippocampal synaptic plasticity in the sdy mutants as DHPG-induced long-term depression (LTD) at CA1 excitatory synapses was significantly reduced. Behavioral data suggest that the mGluRI hypofunction may underlie some of the cognitive abnormalities described in sdy mice as the administration of CDPPB (3-cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl benzamide), a positive allosteric modulator of mGluR5, rescued short-term object recognition and spatial learning and memory deficits in these mice. Taken together, our data suggest a novel role of dysbindin-1 in regulating mGluRI functions.